AN ANALYSIS ON FACTORS INFLUENCING THE STUDENTS’ WRITING SKILL - Herdi Herdi (Universitas Lancang Kuning, 2015)
The problem of the research is factors that influencing the students’ writing skill. This research wasconducted at English Education Department FKIP Lancang Kuning University, Pekanbaru. Using DescriptiveResearch focusing on the second year students of class A consisting of twenty five students. This research tries to explain the factors influencing the improvement of the students’ writing skill. The instruments of this research were observation, field notes, and interview. After analyzing the data, it was found that factors influence the improvement of the students’ writing skill were material, media, classroom activities, classroom management, teacher’s strategy, and teacher’s approach. In conclusion, materials, media, classroom activities, classroom management, teacher’s strategy, and teacher’s approach are factors that influence the students’ writing skill.